Postural control of individuals with chronic stroke compared to healthy participants: Timed-Up-and-Go, Functional Reach Test and center of pressure movement - Portnoy, Sigal; Reif, Shlomit; Mendelboim, Tom; Rand, Debbie (European journal of physical and rehabilitation medicine, 2017)
Balance impairments are common following stroke, and may lead to loss of independent functional mobility and falls. Previous studies strived to come up with precise measures of postural control, which will provide a better prognostic power for the health status and safety of the individual. To date, the degree of difference in postural control measures between individuals with chronic stroke and healthy participants is not reported. Also there are no reported correlations between these measures and the Timed-Up-and-Go (TUG) and the Functional Reach Test (FRT). The aims of this study were: 1) to compare balance measures between young and older healthy participants and individuals with chronic stroke; 2) to assess correlations between TUG and FRT to center of pressure (COP) movements performed during four conditions; and 3) to determine the COP measures that best explain the variance in TUG and Functional Independence Measure (FIM). Cross-sectional study. Community. Thirteen young (mean±SD age 25.4±1.1), 11 older (mean±SD age 64.5± 3.5) healthy adults and 21 individuals 6-18 months post-stroke (mean±SD age 61.4 ±10.1). Measurements of COP were recorded while the subjects stood barefoot on a pressure-measuring pad during four conditions: FRT, quiet standing for 10s with eyes open and eyes closed, and sit-to-stand. The TUG was also administered. Participants filled the Activity-specific balance confidence scale (ABC), and their independence in basic activities was rated using the FIM. They also reported the number of falls since stroke onset. Between-group differences were significant. Moderate correlations between pressure-related measurements to the FRT and TUG were found. The COP path during sit-to-stand (Beta=0.971, P<0.001) and the mean COP velocity (Beta=-0.293, P=0.011) explained 67.4% of the variance of the TUG (F=44.4, P<0.001). The variance of the FIM was best explained by the COP length during sit-to-stand (Beta=-0.789, P<0.001) (R2=0.600 [F=28.0, P<0.001]). Different patterns of most of the recorded postural control parameters were exhibited in healthy individuals compared to individuals with stroke. Several COP movement variables collected during simple and quick tasks were significant predictors of functional test scores. These measurements might shed more light on the postural control mechanisms in balance-impaired populations, therefore potentially improve the treatment of postural control.